Community support for license plate recognition. Issue 1 (11th March 2014) - M. Merola, Linda; Lum, Cynthia; Cave, Breanne; Hibdon, Julie
Abstract : Purpose: – Although the use of license plate recognition (LPR) technology by police is becoming increasingly common, no empirical studies have examined the legal or legitimacy implications of LPR. LPR may be used for a variety of purposes, ranging from relatively routine checks of stolen vehicles to more complex surveillance functions. The purpose of this paper is to develop a "continuum of LPR uses" that provides a framework for understanding the potential legal and legitimacy issues related to LPR. The paper then analyzes results from the first random-sample community survey on the topic. Design/methodology/approach: – Random-sample survey ( n =457). Findings: – The paper finds substantial support for many LPR uses, although the public also appears to know little about the technology. The survey also reveals that the public does not regard the uses of LPR as equivalent, but rather support is qualified depending upon the use at issue. Originality/value: – Previous research has not systematically categorized the wide variety of LPR uses, an oversight which has sometimes led to implicit consideration of these functions as if they are equivalent in their costs and benefits. To assist agencies concerned with community responses to LPR use, the paper points to a number of factors tending to decrease support for LPR, namely, the extent to which a use involves purposes unrelated to vehicle enforcement, the extent to which a function involves prolonged storage of individuals' travel data, and the extent to which a use is perceived as impacting "average" members of the community.